English Medium Instruction in Indonesian Higher Education: A Systematic Literature Review Using PRISMA - Bukhori Bukhori; Wahyu Suhendra Waruwu; Neni Fitri Dwi Suryani; Titi Wadarsah; Fitria Khairiah; Elsa Mulia Adha (Institut Teknologi Pendidikan Indonesia, 2026)
This study examines the implementation of English Medium Instruction (EMI) in Indonesian higher education through a qualitative Systematic Literature Review (SLR) using the PRISMA framework. The review focuses exclusively on journal articles indexed in ERIC published between 2021 and 2025. The purpose of this study is to identify the benefits, challenges, and perceptions related to EMI implementation in the Indonesian context. Data were collected through systematic searching, screening, eligibility assessment, and thematic analysis. The findings indicate that EMI positively contributes to students’ English proficiency, academic confidence, and international exposure. However, challenges such as limited English competence, classroom anxiety, comprehension difficulties, and inadequate lecturer preparation remain significant issues. The review concludes that successful EMI implementation in Indonesian higher education requires institutional support, teacher training, and appropriate language policies.